The Effect Cuttings Part and Planting Media Composition to The Growth Seeds Dragon Fruit (Hylocereus costaricensis (Web) Britton & Rose) - Adli Rifqi Alka Siregar; Lisa Mawarni; Chairani Hanum (Jurnal Pertanian Tropik, 2019)
The factors affect the success of cuttings is composition of planting media and position of planting materials. The experiment aims to determine response growth dragon fruit seeds on various composition of planting media. It was conducted in the field of research Agriculture Faculty, North Sumatra University, Medan with the height about 32 meters above sea level on April to August 2016. The design used factorial randomized block design with two factors and three repetitions. The first factor is part of the stem cuttings with three variety i.e. bottom stem, center stem, top stem and the second factor is planting media with four variety i.e. sand 100%, sand 50% + sludge 50%, sand 50% + empty palm fruit bunches (EPFB) 50%, sand 50% + sludge 25% + EPFB 25%. Data were analyzed using analysis of variance followed by Duncan’s multiple range test (DMRT). The results showed that part of the stem cuttings hasn’t effect to all observation parameters.The best planting media composition is present in the treatment sand 50% + sludge 25% + EPFB 25%. Interaction about both of factors hasn’t effect to all observation parameters.